مناهج التّعليم الدّينيّ وتشكيل هويّة الطفل في مجتمع متعدّد الثقافات دراسة ميدانيّة حول المدارس الإسلاميّة في مقاطعة جنوب هولندا - محسن بن علي زمزمي
One of the most critical challenges facing the Muslim family and the Islamic school in the Netherlands is the formation of the child's identity according to an equation that harmoniously combines both his belonging to Islam and to the multicultural Dutch society. The curricula of Islamic religious education are considered one of the essential tools facing this challenge. This study aims to examine fourteen values that help in the harmonious formation of the child's Dutch Islamic identity in its three dimensions: collective, relational, and personal, by determining to what extent these values are present in the Islamic religious education curricula. This study relied on the descriptive approach, according to a comprehensive survey method, using a questionnaire sent to the research community consisting of all religious education teachers in the Islamic primary schools in the province of South Holland. In analyzing the data, the study opted for descriptive analysis methods. The interview was also used with a sample of the research community. In analyzing the interview data, the study relied on the conceptual framework of the research, using the deductive approach. Perhaps, the most important results of the survey are the general orientation for neutrality of the research community regarding the presence of four values, which are: human brotherhood, citizenship, at-tazkiyah (cleaning and development), and al-omran (being constructive), and also the general orientation for neutrality regarding the curricula's observance of cultural pluralism in the family and school environments of the child in presenting the values of the relational dimension. The study made recommendations in relation to the content of Islamic religious education curricula to enhance their ability to contribute to the desired formation of the child's identity within the pluralistic Dutch social context. It also recommended benefiting from the experience of this research in similar social settings contexts.